Co-Cultivation Growth of Escherichia coli and Staphylococcus aureus as Two Common Dairy Contaminants - Alžbeta Medveďová; Romana Györiová; Veronika Lehotová; Ľubomír Valík (Polish Journal of Food and Nutrition Sciences)
The overgrowth of spoilage and pathogenic bacteria may pose risk to consumers health and cause technological and economic losses. Hence, interactions among S. aureus 2064 and E. coli BR in dependence of incubation temperature and different initial counts of both microorganisms were quantitatively described based on cultivation experiments and predictive models. Statistically insignificant differences (p≥0.05) between growth rates of E. coli at different initial concentrations suggest that the growth rates of E. coli in co-cultivation with S. aureus were affected only by incubation temperature. The growth of E. coli can be reliably predicted ( R 2 =0.968; A f =1.160) based on the equation √μ=0.0283 (T-T_min )+0.1038. The growth of S. aureus during its co-cultivation with E. coli was influenced by incubation temperature and the presence of E. coli as well. It was documented by relatively high discrepancies indexes ( D f 23.9-43.9%) and also by differences between growth rates at different initial microbial concentrations. These results may help in better understanding of interrelationships during sensitive foods production ( e.g. without temperature treatment or those with intensive manual handling).